2006
DOI: 10.1088/0954-3899/32/8/001
|View full text |Cite
|
Sign up to set email alerts
|

Quark stars within relativistic models

Abstract: Lately, it has been suggested that strange (quark) stars can be responsible for glitches and other observational features of pulsars. Some discussions on whether quark stars, if really exist, are bare or crusted are also a source of controversy in the recent literature. In the present work we use the Nambu-Jona-Lasinio model, known to incorporate chiral symmetry, necessarily present in the QCD formalism, in order to describe quark star properties. We compare our results for the stars and the features of the mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(68 citation statements)
references
References 64 publications
1
66
1
Order By: Relevance
“…Moreover, in Ref. [55] it was shown that within the NJL a much larger electron chemical potential is expected at the surface, allowing more easily for a mantle to exist. Understanding how this mantle could be affected in the presence of a magnetic field is an interesting question that, however, is beyond the scope of the present work.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in Ref. [55] it was shown that within the NJL a much larger electron chemical potential is expected at the surface, allowing more easily for a mantle to exist. Understanding how this mantle could be affected in the presence of a magnetic field is an interesting question that, however, is beyond the scope of the present work.…”
Section: Resultsmentioning
confidence: 99%
“…This effect is clearly seen by comparing the pressure for ρ = 3ρ 0 corresponding to u and d quark matter with restored chiral symmetry with the pressure obtained for either ρ = 2ρ 0 or ρ = 5ρ 0 as a function of B: In the first case chiral symmetry is still not completely restored and in the second the onset of s quark has occurred. If a quark model with complete chiral symmetry restored, such 065205-8 as the MIT bag model, or a model without the strangeness degree of freedom, such as the su(2) NJL, is used to describe β-equilibrium quark matter, a different behavior will probably occur for B 10 18 G and ρ > 0.5 fm −3 right until the star center, e.g., ρ ∼ 1.2 fm −3 [21,55]; in particular, both pressure contributions will be coincident.…”
Section: Final Remarksmentioning
confidence: 99%
“…5, a mass-radius plot of compact object. Theoretically, pulsars may consist of hadronic matter only (Menezes & Providência 2004a), hadronic and quark matter (hybrid stars) either bearing or not a mixed phase (Menezes & Providência 2004b;Panda et al 2004;Tatsumi et al 2003) or quark matter only (Menezes et al 2006a;Ivanov et al 2005;Li et al 1999). All calculations depend on choosing of appropriate equations of state based on nuclear physics and thermodynamics requirements, which enter as input to the Tolman-OppenheimerVolkoff equations.…”
Section: Pulsar: Neutron Star or Quark Star?mentioning
confidence: 99%
“…Typically this abundance does not exceed 1/3 [19]. We mentioned above that we can take that n u = n d = n s = n 0 /3 in QS as a limiting case.…”
Section: Introductionmentioning
confidence: 99%